2017
DOI: 10.1108/imds-11-2016-0500
|View full text |Cite
|
Sign up to set email alerts
|

Consumer online flow experience

Abstract: Purpose The purpose of this paper is to investigate the consumer experience of flow in an online consumer shopping environment and use online consumer participants to examine how consumer pursuit of shopping value links in turn affects their satisfaction and unplanned purchase behavior. Design/methodology/approach The research model was tested using the data collected from 363 valid questionnaires. Structural equation modeling was employed to verify and validate the research model. Findings The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 49 publications
5
59
0
Order By: Relevance
“…Hedonic value in shopping represents the overall emotional impressions that are being generated at the time of shopping (Collins, Kavanagh, Cronin, & George, 2014). Numerous shopping-related activities such as searching required products in shelves, observing the display of various companies' window; interacting with store personnel, doing fun at the time of bargaining make the shopping trip to the customers truly enjoyable (Lee & Wu, 2017).…”
Section: Hedonic Valuementioning
confidence: 99%
“…Hedonic value in shopping represents the overall emotional impressions that are being generated at the time of shopping (Collins, Kavanagh, Cronin, & George, 2014). Numerous shopping-related activities such as searching required products in shelves, observing the display of various companies' window; interacting with store personnel, doing fun at the time of bargaining make the shopping trip to the customers truly enjoyable (Lee & Wu, 2017).…”
Section: Hedonic Valuementioning
confidence: 99%
“…Concentration has been verified to have positive effect on consumers' online shopping experience in western countries. For example, Lee and Wu (2017) demonstrated that concentration positively influences online consumers utilitarian value. Ettis (2017) examined the effects of concentration on online purchase intention and online store revisit intention and found they exist.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Utilitarian value can be defined as an overall judgment of functional benefits and sacrifices [25,26]. In general, the utilitarian value refers to whether functions of products meet consumers' expectation [27], including economic value such as money, convenience, and saving time [28][29][30]. However, an increasing number of consumers pay attention to the importance of hedonic value [13,31].…”
Section: Utilitarian and Hedonic Valuesmentioning
confidence: 99%